Analysis of Breach of Contract in Online Sales Agreements Based on the Civil law - Pramudito, Mariana; Permadi (Yayasan Cinta Negara, 2025)
This study examines the legal analysis of breach of contract in online sales agreements within the framework of the Indonesian Civil Code. The rapid growth of e-commerce has transformed traditional contractual relations, bringing forth new challenges in ensuring compliance and accountability in digital transactions. While online sales agreements are governed by general contract principles, their execution often encounters unique breaches such as non-delivery, defective goods, or refusal of payment. The research explores how the Civil Code—particularly provisions related to default (wanprestasi)—is applied to online transactions, and how these provisions intersect with contemporary practices in electronic commerce. The study utilizes a normative juridical approach by analyzing relevant statutory regulations, legal doctrines, and judicial precedents. It identifies key elements of contractual obligations, types of breaches, legal consequences for parties in default, and available legal remedies. The findings highlight that while the Civil Code provides a sufficient legal foundation for contractual enforcement, it lacks specificity for addressing the complexities of digital sales environments. Therefore, integration with technological regulations and consumer protection laws is essential to enhance legal certainty and justice. This research contributes to the development of digital contract law by providing recommendations for harmonizing traditional legal doctrines with modern e-commerce practices. It is expected to serve as a reference for legal practitioners, business actors, and regulators in interpreting and applying breach of contract rules in the context of online transactions